POST-SPACE SEBAGAI BENTUK PERLAWANAN IMIGRAN TERHADAP TATANAN KOLONIAL DALAM NOVEL BRICK LANE KARYA MONICA ALI - Ikbal, Muhammad; Sudibyo, Sudibyo (ATAVISME, 2022)
Brick Lane's is a post-colonial literary work that raises the issues of the Bangladeshi diaspora in England. The raise of diaspora writers who settled in Europe and America has colored modern world literature. The ideas of diaspora writers do not only present works with monolithic ideas, they have also presented various spatial constructions and identities about immigrants living in the Western world. This research was conducted as an effort to answer the formulation of the problem as follows: (1). What is the postcolonial spatial response in Brick Lane Monica Ali's novel? (2). How about urban space construction and postcolonial spatial strategy in the novel Brick Lane? This study uses qualitative research methods to explore how the author constructs postcolonial space and offers post-space in his work. Data was collected inductively through the depiction of characters in the novel and classified for later analysis using Spatial Politics Sara Upstone's theory. The results of this study indicate that the authors attempt to present chaos as a postcolonial spatial response. The chaos presented by the author appears when certain individuals in the novel feel discriminated against in a space with colonial-created boundaries and orders, either because of their identity or social class. The author also constructs city space by offering a strategy displacement in the form of transferring a sense of belonging to the smaller things that construct urban space, and the relationships between figures that make individuals feel comfortable with their existence.